Legal opacity, narcotics laws, and drug seizures - Ninon Moreau-Kastler; Farid Toubal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We show that legal opacity is a strong factor in drug trafficking. We develop a new framework that illustrates how legal opacity influences countries' seizure rates. Legal opacity reduces the detection of illicit flows and increases their volumes because it lowers trafficking costs. We use detailed information from financial systems evaluations, international standards cooperation mechanisms, and economic indicators to construct a new worldwide legal opacity index that covers each of the last two decades. Our empirical results reveal the importance of legal opacity and the enforcement of narcotics laws for drug seizure rates.
Keywords: K42; O17; F50; 330; opacity; drug trafficking; illicit flows; seizures; narcotics laws; narcotics